Study on Burning and Thermal Decomposition Properties of HTPB Propellant Containing Synthesized Micro‐nano Ferric Perfluorooctanoate. Issue 3 (11th January 2019) - Zhen, Fei; Zhou, Xu‐Yuan; Wang, Li‐Qiong; Yang, Rong‐Jie; Huang, Feng‐Lei
Abstract: A novel micro‐nano ferric perfluorooctanoate [Fe(PFO)3 ] was prepared and added in AP/Al/HTPB composite solid propellant as a catalyst to study its effects on burning and thermal decomposition properties of the propellant. To further discuss the possible thermal mechanism of the propellant containing Fe(PFO)3, the major effects of Fe(PFO)3 catalyst on Al were investigated by differential scanning calorimetry (DSC), thermogravimetric analysis (TG) and X‐ray diffraction (XRD). Results show that By adding 3 w.t.% Fe(PFO)3, the burning rate could increase by 27.8 % at 3 MPa, meanwhile, the pressure exponent decreased. The aggregation/agglomeration process of the propellant containing Fe(PFO)3 efficiently suppressed, and the particle size of condensed combustion products decreased clearly. In addition, Fe(PFO)3 could reduce the thermal decomposition temperature of the propellant and enhance the heat release. Thermite reaction between decomposition products of Fe(PFO)3 and Al was triggered at 635 °C, resulting in heat release and formation of α‐Al2 O3 . Abstract :